Pembentukan Identitas Tionghoa Muslim di Kalangan Persatuan Islam Tionghoa Indonesia Semarang - Devi Ratnawati; Nurhadi Nurhadi; Abdul Rahman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The New Order government encouraged ethnic Chinese Indonesians as the local population, resulting new identity as Chinese Muslims, then the group formed PITI. This research is analyzing the forming of Chinese Muslim socio-cultural identity among PITI from the perspective of Tajfel and Turner's social identity theory. The descriptive qualitative research method used in this research, and the data obtained from semi-structured in-depth interviews, observations, and documentation and/or literature studies. The results showed that Chinese Muslims tried to maintain and gain a positive social identity. It can be seen from individual and collective efforts to form different socio-cultural identities, some Muslim Chinese identify Chinese socio-cultural, some identify Javanese socio-cultural.